2010
DOI: 10.1038/ajh.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Echocardiography as a Predictor of Events in Patients With Left Ventricular Hypertrophy

Abstract: LV mass independently predicts mortality, even when EE data are considered. EE provides significant information for predicting events in patients with LVH and known/suspected CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In patients with left ventricular hypertrophy undergoing exercise echocardiography, left ventricular mass index predicted mortality, and failure to increase ejection fraction with exercise predicted cardiovascular death and nonfatal myocardial infarction [29]. A study in patients with left ventricular hypertrophy found that ischemic changes at peak exercise predicted overall mortality and major cardiac events [30]. Finally, a study evaluating the effects of left ventricular geometry on exercise capacity found that patients with concentric hypertrophy demonstrated less exercise capacity and attenuated hemodynamic responses to exercise compared with patients with eccentric hypertrophy [31].…”
Section: Key Pointsmentioning
confidence: 99%
“…In patients with left ventricular hypertrophy undergoing exercise echocardiography, left ventricular mass index predicted mortality, and failure to increase ejection fraction with exercise predicted cardiovascular death and nonfatal myocardial infarction [29]. A study in patients with left ventricular hypertrophy found that ischemic changes at peak exercise predicted overall mortality and major cardiac events [30]. Finally, a study evaluating the effects of left ventricular geometry on exercise capacity found that patients with concentric hypertrophy demonstrated less exercise capacity and attenuated hemodynamic responses to exercise compared with patients with eccentric hypertrophy [31].…”
Section: Key Pointsmentioning
confidence: 99%
“…There is wide information regarding the incremental diagnostic and prognostic value of stress echocardiography over clinical characteristics, resting echocardiography and exercise testing in different populations and scenarios, particularly for patients with already demonstrated CAD, intermediate pre-test probability of CAD, and/or resting ECG abnormalities [19][20][21][22][23][24][25]. In patients with right bundle branch block, the number of interpretable leads is sometimes limited.…”
Section: Stress Echocardiography In Different Populationsmentioning
confidence: 99%
“…In patients with known or clinically suspected left ventricular hypertrophy, exercise echocardiography has been shown to be more accurate than exercise ECG testing for the detection of CAD 27 and to provide incremental prognostic information in the prediction of death and other major adverse cardiac events. 24,25 Moreover, the anginal symptoms in patients with left ventricular hypertrophy may in part be related to coronary microvascular dysfunction and are not always easy to discern from dyspnoea caused by an associated left ventricular diastolic dysfunction. Transthoracic Doppler may allow the assessment of coronary flow velocity reserve at rest 28 and to monitor changes of pulmonary pressure changes and diastolic left ventricular function parameters 29 during exercise that may increase significantly in patients with an underlying concealed left ventricular diastolic dysfunction.…”
Section: Jm Vrintsmentioning
confidence: 99%
“…Furthermore, patients with left ventricular hypertrophy constitute a high-risk subgroup with an almost three times increased risk of cardiovascular morbidity and mortality. [24][25][26] Therefore, refined analysis of exercise ECG should be combined with exercise echocardiography in order to increase the diagnostic accuracy and the prognostic predictive power in this subset of patients. In patients with known or clinically suspected left ventricular hypertrophy, exercise echocardiography has been shown to be more accurate than exercise ECG testing for the detection of CAD 27 and to provide incremental prognostic information in the prediction of death and other major adverse cardiac events.…”
Section: Jm Vrintsmentioning
confidence: 99%